Similar operators generated by the nonlocal problems for elliptical second-order equations - Baranetsky , Ya. O. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The spectral properties and properties of the L^2-solutions of the nonlocal problem for second-order linear elliptic nondivergent-type equations that represent an isospectral disturbance of the Dirichlet problem are investigated.